2020
DOI: 10.1002/lary.29003
|View full text |Cite
|
Sign up to set email alerts
|

The Family Impact of Having a Child with a Tracheostomy

Abstract: Objectives: Measure the quality of life among families with children with tracheostomies. Methods: We performed a prospective cross-sectional analysis of families with children with tracheostomies utilizing the PedQL Family Impact Module-a validated quality of life assessment. We determined if scores were impacted by demographics using regression analysis. We also compared the tracheostomy sample's scores to a previously published cohort of children with severe cerebral palsy and birth defects that required ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 30 publications
(39 reference statements)
1
22
0
Order By: Relevance
“…Previous work concluded that families of children with tracheostomies have mean PedsQL scores similar to families with medically fragile children and lower than those with healthy children. 28 No study has looked at quality of life for families of children with tracheostomies based on community disadvantage. Inclusion of this secondary metric, focusing on family-reported impact, reflects a growing emphasis on quality when assessing health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work concluded that families of children with tracheostomies have mean PedsQL scores similar to families with medically fragile children and lower than those with healthy children. 28 No study has looked at quality of life for families of children with tracheostomies based on community disadvantage. Inclusion of this secondary metric, focusing on family-reported impact, reflects a growing emphasis on quality when assessing health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The program has previously published outcomes related to decannulation, mortality, and quality of life after tracheostomy placement. [26][27][28] Therefore, it is well-suited to examine socioeconomic effects on risk factors, hospital courses, and readmissions after tracheostomy placement.…”
Section: Introductionmentioning
confidence: 99%
“…This program at Children's Medical Center Dallas has previously published reports on perioperative outcomes, quality of life, and socioeconomic factors. 6,[13][14][15][16] It is therefore suited to analyze mortality events after tracheostomy. The primary objective of this study was to prospectively characterize mortality among tracheostomy-dependent children.…”
Section: Introductionmentioning
confidence: 99%
“…Children are prospectively enrolled in a registry at tracheostomy placement, allowing a multidisciplinary team of providers to manage patients and collect outcome metrics. This program at Children's Medical Center Dallas has previously published reports on perioperative outcomes, quality of life, and socioeconomic factors 6,13–16 . It is therefore suited to analyze mortality events after tracheostomy.…”
Section: Introductionmentioning
confidence: 99%
“…The Children's Health Airway Management Program (CHAMP) prospectively follows children with tracheostomies and has previously published reports on perioperative outcomes, quality of life, and socioeconomic factors. [10][11][12][13][14] It is therefore suitable to study persistent tracheocutaneous fistulas.…”
Section: Introductionmentioning
confidence: 99%